Atomic Force Microscopy Provides New Mechanistic Insights into the Pathogenesis of Pemphigus - Vielmuth, Franziska; Spindler, Volker; Waschke, Jens (Frontiers in Immunology, 2018)
Autoantibodies binding to the extracellular domains of Dsg3 and Dsg1 are critical in the pathogenesis of pemphigus by mechanisms leading to impaired function of desmosomes and blister formation in the epidermis and mucous membranes. Desmosomes are highly organized protein complexes which provide strong intercellular adhesion. Desmosomal cadherins such as desmogleins (Dsg), proteins of the cadherin superfamily which interact via their extracellular domains in Ca2+-dependent manner, are the transmembrane adhesion molecules clustered within desmosomes. Investigations on pemphigus cover a wide range of experimental approaches including biophysical methods. Especially atomic force microscopy (AFM) has recently been applied increasingly because it allows the analysis of native materials such as cultured cells and tissues under near-physiological conditions. AFM provides information about the mechanical properties of the sample together with detailed interaction analyses of adhesion molecules. With AFM, it was recently demonstrated that autoantibodies directly inhibit Dsg interactions on the surface of living keratinocytes, a phenomenon which has long been considered the main mechanism causing loss of cell cohesion in pemphigus. In addition, AFM allows to study how signaling pathways altered in pemphigus control binding properties of desmogleins. More general, AFM and other biophysical studies recently revealed the importance of keratin filaments for regulation of desmoglein binding and keratinocyte mechanical properties. In this mini-review, we reevaluate AFM studies in pemphigus and keratinocyte research, recapitulate what is known about the interaction mechanisms of desmosomal cadherins and discuss the advantages and limitations of AFM in these regards.